Optimization of single-channel active noise control performance in a plenum window using the surface impedance approach - Tan, Johann Kay Ann (2024)
The use of active noise control (ANC) implementation in plenum window design is investigated in this study. Various simulated configuration of a single-channel ANC is performed using the surface impedance approach (SIA) in order to optimize ANC performance. Based on a systematic search procedure, the optimal control source placement is found for a control source localized at the central bottom and central depth of the plenum window, near the window's inlet from which primary noise is impinging. The optimized ANC configuration provides an average attenuation benefit of 9.2 dB between 200 and 630 Hz. Error sensor location in the plenum window cavity is not crucial for the ANC system and does not need to be rigid. A dual-channel ANC system with control sources at both sides of the plenum window can extend the frequency of control to ∼800 Hz with an average attenuation of 7.6 dB. Additionally, an experimental case study using a real-time ANC system is conducted with a built-to-scale plenum window in an apartment informed by findings from the SIA simulation, demonstrating the usefulness of the SIA in ANC optimization process.